HUBUNGAN KECERDASAN EMOSIONAL DAN SELF-EFFICACY DENGAN EFEKTIVITAS KINERJA PADA PERAWAT PELAKSANA DI RUANG RAWAT INAP - Najwah Ayu Firnanda; Tatiana Siregar (Program Studi S1/DIII-Keperawatan Universitas Imelda Medan, 2026)
Low nurse performance in hospitals is an important issue that requires serious attention, as suboptimal performance may affect the overall quality of hospital services. Nurse performance that remains relatively low is closely related to individual internal factors, such as emotional intelligence and levels of self-efficacy. This study aimed to analyze the relationship between emotional intelligence and self-efficacy with the effectiveness of performance among staff nurses in the inpatient wards of Hospital X. This study employed a quantitative method with a cross-sectional approach and involved the entire population as the research sample, totaling 116 respondents. Data analysis was conducted using frequency distribution to describe respondent characteristics, Chi-Square tests to examine relationships, and Multiple Logistic Regression analysis using SPSS. The results of the multivariate analysis showed no significant relationship between emotional intelligence (p-value = 0.188) and self-efficacy (p-value = 0.108) with the effectiveness of nurse performance in the inpatient wards of Hospital X. This study is expected to serve as a reference for hospital management in paying attention to factors that may influence nurse performance effectiveness. In addition, the findings may be used as a basis for developing self-development training programs to support more effective nurse performance.